THE IMPLEMENTATION OF THE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) COOPERATIVE LEARNING MODEL IN IMPROVING STUDENTS’ LEARNING OUTCOMES ON SMALL BALL GAME MATERIALS FOR YEAR VII-A STUDENTS OF MTSN 3 WEST ACEH IN 2020-2021 ACADEMIC YEAR - Badrussalim Badrussalim; Riki Irawan (Pedagogi: Jurnal Ilmiah Pendidikan, 2021)
This study aims "To find out whether the use of the Student Teams Achievement Division (STAD) Cooperative Learning Model can Improve Students’ Learning Outcomes on Small Ball Game Materials for Year VII-A Students of MTsN 3 West Aceh in 2020-2021 academic year. The research sample of this study was Year VII-A class with the total number of students was 23 students. This study used Classroom Action Research (CAR) with the methods of observation, data collection, tests, documentation and data analysis. This study used two cycles to determine the learning outcomes of the students using Student Teams Achievement Division (STAD) type of cooperative learning model in small ball game material. The results of this study indicated that the Student Teams Achievement Division (STAD) type of cooperative learning model can improve students’ learning outcomes in small ball game material for year VII-A students of MTsN 3 West Aceh in 2020-2021 academic year. From the data obtained, the percentage of the learning outcomes on the small ball game material in the first cycle of classical completeness was 47.82%, and in the second cycle was 82.60%. This meant that there was an increase in completeness, namely 5 students (15.63%). Based on the achievement of the students’ activity that was 86.66%, it can be said that the learning outcomes on the small ball game material with the Student Teams Achievement Division (STAD) type cooperative learning model in cycle II was successful because the results obtained have exceeded the students’ learning mastery indicator, which is 80 %.